Design and Realization of Dynamic Obstacle on URWPSSim2D - Shuqin Li; Xiaohua Yuan; Xiao Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Simulation system is charged with the strategy validation and dual team meets, and as the 2-dimensional simulation platform for underwater robotic fish game, URWPGSim2D is the assigned platform for Chinese underwater robot contest and Robot cup underwater program. By now on URWPGSim2D, there is only static obstacles，thus short of changeableness. In order to improve the changeableness and innovation of robotic fish contest, to extend the space for the programming of contest strategy, and to increase the interest, this paper study the design of dynamic obstacles on URWPGSim2D, and design and implement two kinds of dynamic obstacles, which are the evadible dynamic obstacle and the forcing dribbling obstacle. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3996